Assessment of quality of life of geriatric population in Nawabganj, Unnao - Raazi, Jamil; Rahman, Ayesha K. (International Journal Of Community Medicine And Public Health, 2019)
Background: The quality of life (QOL) among geriatrics is a neglected issue especially in developing countries including India. It is a broad-ranging concept affected in a complex way by the individual’s physical health, psychological state, level of independence, social relationships, and their relationships to the environment. The study was done to assess the QOL and morbidity patterns of people aging 60 or above in urban Nawabganj, Unnao and to correlate the QOL with various sociodemographic factors. Methods: A community based cross-sectional study was conducted among 220 elderly subjects in urban field practice area of Saraswati Medical College, Unnao from February to April 2018. The data on QOL was assessed by World Health Organization Quality of Life BREF (WHOQOL-BREF). The socio-demographic characteristics and morbidity conditions were recorded by using structured questionnaire. The independent sample t test was used to compare the mean scores. Results: A total of 220 subjects participated in the study. Majority (64.09%, 141) were in the 60-69 years’ age-group. Around 40% of the total was males and 64.54% (142) were literate. About 2/3 of them 62.72%, (138) lived with their partners and 66.81% (147) lived in nuclear families. The most common morbidity was musculoskeletal problems (44.54%) followed by hypertension (36.81%) and diabetes (28.63%). The independent t-test showed that QOL was significantly low among those in illiterate, those living in nuclear families and those living separate, widow/widower and divorced. Conclusions: The quality of life score of geriatric population was found to be average with the lowest score in social relationships.